1991
DOI: 10.1017/s0017089500008168
|View full text |Cite
|
Sign up to set email alerts
|

Free right type A semigroups

Abstract: Introduction. The relation i£* is defined on a semigroup 5 by the rule that a!£*b if and only if the elements a, b of S are related by Green's relation =2" in some oversemigroup of 5. A semigroup S is an E-semigroup if its set £(5) of idempotents is a subsemilattice of S. A right adequate semigroup is an £-semigroup in which every i?*-class contains an idempotent. It is easy to see that, in fact, each i?*-class of a right adequate semigroup contains a unique idempotent [8]. We denote the idempotent in the if-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…If X is a representative Σ-tree for X ∈ UT 1 (Σ) then X (+) is the isomorphism type of [9] Free adequate semigroups 373 the idempotent tree with the same underlying graph and start vertex as X , but with end vertex the start vertex of X . Dually, X ( * ) is the isomorphism type of the idempotent tree with the same underlying graph and end vertex as X , but with start vertex the end vertex of X .…”
Section: Algebra On Treesmentioning
confidence: 99%
“…If X is a representative Σ-tree for X ∈ UT 1 (Σ) then X (+) is the isomorphism type of [9] Free adequate semigroups 373 the idempotent tree with the same underlying graph and start vertex as X , but with end vertex the start vertex of X . Dually, X ( * ) is the isomorphism type of the idempotent tree with the same underlying graph and end vertex as X , but with start vertex the end vertex of X .…”
Section: Algebra On Treesmentioning
confidence: 99%
“…We direct the reader to [11] for further details on RC-semigroups and their relatives, but of particular interest are weakly right ample semigroups (see [7] for the left-sided version), and right type-A semigroups (see [5] for example). These closely related classes have seen reasonably extensive research.…”
Section: Rc-semigroups Slorc's and Agreeablesmentioning
confidence: 99%
“…The RC-semigroup reducts of members of TC generate the variety of twisted RCsemigroups with central closed elements. This variety was examined by Fountain [5] who showed that (after translation from right type-A semigroups to the language of RC-semigroups) it has decidable equational theory. Theorem 6.6 gives us the following contrasting result.…”
Section: Interpreting the Usual Word Problemmentioning
confidence: 99%
See 2 more Smart Citations